Does the modified Glasgow Prognostic Score (mGPS) have a prognostic role in esophageal cancer?. Issue 7 (23rd March 2016) - Walsh, Siun M.; Casey, Sarah; Kennedy, Raymond; Ravi, Narayanasamy; Reynolds, John V.
Abstract : Background: The modified Glasgow Prognostic Score (mGPS), which combines indices of decreased plasma albumin and elevated CRP, has reported independent prognostic significance in colorectal cancer, but its value in upper gastrointestinal cancer is unclear. The aim of this study was to assess the prognostic significance of mGPS in patients with operable esophageal malignancy. Methods: Patients undergoing resection with curative intent between January 2008 and June 2013 were included. The mGPS was scored as 0, 1, or 2 based on CRP(>10 mg/L) and albumin(<35g/L). The mGPS score (0 vs. 1/2 combined) was correlated with patient and tumor characteristics, and operative and oncologic outcomes. Results: Two hundred and twenty‐three patients were included. Median (range) follow‐up was 21(12–70) months. The mGPS was 0 in 174 patients(78%). mGPS was significantly associated with positive nodal status( P  = 0.008) and stage ≥III ( P  = 0.017). There was a significant improvement in overall survival in patients with mGPS = 0 (47.8 vs. 37.5 months, P  = 0.014) but in multivariate analysis, only TNM‐stage and nodal status were found to be independent prognostic indicators. Conclusions: mGPS is associated with advanced stage but has no independent prognostic significance and does not impact on operative outcomes. Consequently, this data does not support its routine application in patient selection or prognostication. J. Surg. Oncol. 2016;113:732–737 . © 2016 Wiley Periodicals, Inc.